PENYELENGGARAAN SISTEM PRESIDENSIL BERDASARKAN KONSTITUSI YANG PERNAH BERLAKU DI INDONESIA - S, Laurensius Arliman (Jurnal Muhakkamah, 2019)
A presidential system government is a government in which the executive position is not accountable to the representative body of the people, in other words the executive power is outside (direct) parliamentary oversight. Not only is presidentialism and a multiparty system a "difficult combination", it also opens up opportunities for deadlocks in executive and legislative relations which then impact on the instability of presidential democracy. The government system in the constitutional trajectory that applies is as much as 5 times, it is divided into: three times using a presidential system, one time Quasi Parliamentary (Quasi Parliamentary), and one time using a presidential system. In a coalition government, political parties are not responsible for raising the president in the election so political parties tend to leave the president who is no longer popular. Presidential elections are always there before the eyes so that political parties try as much as possible to keep distance from various presidential policies, which may be good, but not populist. The reason for the incompatibility, is likely to bring down the government unconstitutionally. The magnitude of the opportunity for unconstitutional change of government is very relative because in a presidential system it is very difficult to reduce an elected president. We can feel the multi-party effects in Indonesia, namely the difficulty of the President to make decisions relating to the problems of national life and strategic state. Actually the position of the President is very strong because the president is directly elected by the people not elected by the DPR. But in the case of the issuance and ratification of the presidential legislation the DPR needs support.